Buli dalam kalangan pelatih di pusat pemulihan juvana - Nazirah Hassan; Daniella Mokhtar (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study investigates bullying and victimisation in juvenile rehabilitation institutions in Malaysia, where research on this phenomenon has been particularly limited. It examines the prevalence of bullying and victimisation in these settings and investigates the role of personal characteristics and aspects of institutional environments, and explores how these factors relate to bullying behaviour. The study comprised a survey completed by 289 male and female young people, aged 12 to 21 years old, in 8 juvenile rehabilitation institutions, using the scale version of Direct and Indirect Prisoner Behaviour Checklist (DIPC-SCALEDr) and the Measuring the Quality of Prison Life (MQPL) instruments. The findings showed that 95 percent of young people reported at least one behaviour indicative of bullying others, and 99 percent reported at least one behaviour indicative of victimisation in a month. Seven predictors were found to underpin bullying behaviour, including three personal characteristics (i.e. time spent in the institution, experiences of punishment inside the institution, and gang membership) and four institutional dimensions (i.e respect; bureaucratic legitimacy; fairness; and family contact). To conclude, bullying behaviour seemed to be normalized in juvenile rehabilitation institutions. As the heart of institution, staff members play an important role to control bullying behaviour amongst young people. The importance of these findings for bullying prevention strategies and directions for future research are discussed.